Institutional Quality of the Business Environment: Some European Practices in a Comparative Analysis - Cosmin Marinescu (Amfiteatru Economic Journal, 2013)
In contemporary economic literature, we can find plenty of theoretical and empirical approaches which seek to highlight the most appropriate factorial variables that are associated with the institutional quality of the business environment. This study presents, in a summarised version, the institutional logic of transaction costs that was substantiated within a scientific research project. In essence, the economic performances of the business environment are circumscribed by the institutions that facilitate or constrain the entrepreneurial initiatives and the economic activity in general. In terms of empirical analysis, the comparative approach of the EU business environments illustrates various exemples of (good or bad) practices with respect to the institutional quality of the business environment. By selecting certain relevant institutional variables, the original character of this research resides in developing an indicator – The Institutional Quality of the Business Environment (hereafter IQBE) which offers a dynamic perspective upon the business environments that characterise both Romania and other EU countries.
Keywords: D02; D23; K11; L26; 330; Institutional Quality of the Business Environment; Transaction Costs; Entrepreneurship; Property Rights